2004
DOI: 10.36076/ppj.2004/7/195
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cervical Medial Branch Blocks in Chronic Neck Pain: A Prospective Outcome Study

Abstract: Background:The high prevalence of persistent neck pain due to involvement of cervical facet joints has been described in controlled studies. Therapeutic interventions utilized in managing chronic neck pain of facet joint origin include intraarticular injections, medial branch nerve blocks, and neurolysis of medial branch nerves by means of radiofrequency.Objective: The objective of this prospective evaluation was to determine the clinical effectiveness of cervical medial branch blocks for therapeutic purposes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Overall, the results show that radiofrequency neurotomy is effective in 54–76% with multiple passes providing multiple lesions taking several hours to perform a single lesion, whereas cervical facet joint nerve blocks with easy performance except that the relief is half that of radiofrequency neurotomy in duration with success rate ranging from 85% to 92% at 12-month follow-up, showing level II evidence with moderate strength of recommendation by the American Society of Interventional Pain Physicians (ASIPP) guidelines utilizing one RCT [ 30 ] and three observational studies [ 89 – 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results show that radiofrequency neurotomy is effective in 54–76% with multiple passes providing multiple lesions taking several hours to perform a single lesion, whereas cervical facet joint nerve blocks with easy performance except that the relief is half that of radiofrequency neurotomy in duration with success rate ranging from 85% to 92% at 12-month follow-up, showing level II evidence with moderate strength of recommendation by the American Society of Interventional Pain Physicians (ASIPP) guidelines utilizing one RCT [ 30 ] and three observational studies [ 89 – 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Major complications were reported to be extremely rare in all the review articles assessed 22,46,48,49) .…”
Section: Management Of Whiplash Using Targeted Injectionsmentioning
confidence: 97%
“…CC BY-NC-ND 4.0 (https://creativecommons.org/licenses/by-nc-nd/4.0/). controlled trial that reported up to 85% improvement in functional and pain scores at 2 year followup [47][48][49] . The findings of a systematic review by Boswell et al were more equivocal 33) .…”
Section: Management Of Whiplash Using Targeted Injectionsmentioning
confidence: 99%
“…The cervical facet is an important structure involved in spinal movement, and its fracture or injury often causes loss of spinal stability and spinal nerve injury, which is an important cause of cervical diseases. [1][2][3] However, due to the complex anatomical structure of the lower cervical spine, treatment can be challenging. Most conventional computed tomography (CT) examinations can detect cervical facet injuries or fractures at an early stage, but conventional images are obtained with low-resolution imaging methods and the detection level is insufficient for microstructural analysis.…”
Section: Introductionmentioning
confidence: 99%